Students’ academic procrastination during the COVID-19 pandemic: How does adversity quotient mediate parental social support? - Muarifah, Alif; Rofiah, Nurul Hidayati; Mujidin, Mujidin; Mohamad, Zhooriyati Sehu; Oktaviani, Fitriana (Frontiers in Education, 2022)
The COVID-19 has had a widespread impact on all aspects of life. The government has undertaken numerous restrictive attempts to sever the virus transmission chain. In the education sector, one of the attempts is to apply certain learning models. For instance, the online model has been used in place of the face-to-face one across all academic and non-academic services. Educators have faced several obstacles, including academic procrastination. Academic procrastination refers to intentionally putting off working on an assignment, which negatively influences academic achievement. This study aimed to examine the role of parental social support in academic procrastination with the mediation of the adversity quotient. The subjects consisted of 256 state Madrasah Aliyah students in Magelang aged 15–18 years (M = 16.53, SD = 1.009). Data collection employed the academic procrastination scale, parental social support scale, and adversity quotient scale. Data analysis used descriptive statistics and structural equation modeling (SEM) with the aid of the IBM SPSS 23 and AMOS Graphics 26. The research results showed that all variables fell into the medium category. Parental social support had a negative role on academic procrastination and a positive one on adversity quotient. Meanwhile, the adversity quotient had a negative role in academic procrastination and a significant role as a mediator in the relationship between parental social support and academic procrastination. Therefore, parental social support is required to increase students’ adversity quotient in suppressing academic procrastination. Special attention from parents to students is thus critical during the COVID-19 pandemic, with the mediation of adversity quotient.